2017
DOI: 10.1159/000486593
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Glycoprotein B Genotype Distribution in Italian Transplant Patients

Abstract: Background: The cytomegalovirus (CMV) UL55 gene encodes for a glycoprotein implicated in virus pathogenesis. Based on UL55 polymorphism, CMV has been divided into 4 genotypes. Previous studies investigated the possible role of genotypes in the clinical outcome of infection in different categories of patients; however, few data are available, particularly in the transplant setting and Italian case records. Methods: Phylogenetic analysis through a maximum likelihood tree was used to evaluate the prevalence and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
1
15
0
2
Order By: Relevance
“…Thus, it is currently difficult to draw a conclusion as to whether there is a specific gB genotype that leads to a more severe disease progression. Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141].…”
Section: Gbmentioning
confidence: 99%
“…Thus, it is currently difficult to draw a conclusion as to whether there is a specific gB genotype that leads to a more severe disease progression. Compared to a single gB genotype infection, mixed gB genotype infections are frequently reported in organ/bone marrow transplant recipients and AIDS patients [105,118,125,128,129,152]. Multiple studies have also demonstrated that mixed infections are able to be transmitted in utero [63,68,[74][75][76][77]109,122,134,137,138,141].…”
Section: Gbmentioning
confidence: 99%
“…There is growing evidence that the occurrence of mixed genotype infections serves as a marker of severe or prolonged complications from CMV infections in SOT and HSCT recipients [5,6,25,28,[44][45][46].Whether these observations can be extrapolated to the non-HSCT setting is yet to be elucidated. In agreement with a previous report in immunocompromised patients [5], our data showed that patients who were infected with mixed gB genotypes developed higher initial levels of CMV loads and had significantly more concomitant infection with other HHVs than patients infected with single gB genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Larger epidemiological studies and improved genotype-specific real-time PCR-based assays and high-throughput sequencing technology may reveal a high level of intrahost variability and offer strong evidence that CMV exists as a complex mixture of variants in immunocompromised patients and may also clarify more the epidemiological and the clinical impact of these variants. The genetic profile of infecting viruses and relation to clinical outcome should be investigated, taking into account the host’s innate and adaptive immune responses [ 4 , 8 , 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CMV disease in kidney and liver transplant recipients is associated with an elevated rate of viral load and viral load peak [8]. CMV UL55 gene encodes for a glycoprotein B which involved in several essential steps in CMV virus pathogenesis including virus penetration into cells, cell-to-cell spread, and activation of the immune response gB [9] and is involved in the activation of innate immunity as the major antigen for the induction of neutralizing antibodies. gB antibodies have been of interest because of their therapeutic potential for neutralization [10].…”
Section: Introductionmentioning
confidence: 99%
“…gB antibodies have been of interest because of their therapeutic potential for neutralization [10]. Regarding UL55 polymorphism, CMV has been divided into 4 genotypes (gB1-4) [9]. A fifth gB genotype (gB5) was detected in several AIDS patients [11].…”
Section: Introductionmentioning
confidence: 99%